2020
DOI: 10.1038/s41421-020-0154-2
|View full text |Cite
|
Sign up to set email alerts
|

P53 suppresses SENP3 phosphorylation to mediate G2 checkpoint

Abstract: In response to DNA damage, p53-mediated signaling is regulated by protein phosphorylation and ubiquitination to precisely control G2 checkpoint. Here we demonstrated that protein SUMOylation also engaged in regulation of p53mediated G2 checkpoint. We found that G2 DNA damage suppressed SENP3 phosphorylation at G2/M phases in p53dependent manner. We further found that the suppression of SENP3 phosphorylation was crucial for efficient DNA damage/p53-induced G2 checkpoint and G2 arrest. Mechanistically, we identi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 40 publications
1
13
0
Order By: Relevance
“…[47][48][49][50] The p53induced cell cycle arrest may occur at either G 2 /M or G 1 /S checkpoints, reflecting cell context-specific outcomes in different cells. 47,50,51 Here, we found that Anp32b deletion in HSCs increased quiescent cells and impaired division and proliferation, whereas Anp32b deficiency in LSCs decreased quiescent cells and promoted their cell cycle entry, which was followed by enhanced proliferation and increased apoptosis, supporting that p53 plays different roles in fate decision of HSCs and LSCs as reviewed. 52 Principally, p53 promotes quiescence of HSCs, and the absence of p53 promotes HSC more cell cycle entry, whereas p53 preferentially induces apoptosis of LSCs, [13][14][15][16] although precise function of p53 on LSCs has not been clarified.…”
Section: Discussionsupporting
confidence: 60%
“…[47][48][49][50] The p53induced cell cycle arrest may occur at either G 2 /M or G 1 /S checkpoints, reflecting cell context-specific outcomes in different cells. 47,50,51 Here, we found that Anp32b deletion in HSCs increased quiescent cells and impaired division and proliferation, whereas Anp32b deficiency in LSCs decreased quiescent cells and promoted their cell cycle entry, which was followed by enhanced proliferation and increased apoptosis, supporting that p53 plays different roles in fate decision of HSCs and LSCs as reviewed. 52 Principally, p53 promotes quiescence of HSCs, and the absence of p53 promotes HSC more cell cycle entry, whereas p53 preferentially induces apoptosis of LSCs, [13][14][15][16] although precise function of p53 on LSCs has not been clarified.…”
Section: Discussionsupporting
confidence: 60%
“…Notably, the SUMOylation levels of the proteins are varied in response to mitochondrial stress [24]. As SUMO deconjugation proteases, SENPs have been considered to be the regulators of SUMOylation upon cellular stresses [25][26][27][28].…”
Section: Sumoylation Is a Stress-induced Processmentioning
confidence: 99%
“…The C-terminal phosphorylation of yeast SUMO isopeptidase Ulp2 during mitosis may inhibit its isopeptidase activity (Baldwin et al, 2009). Cdk1mediated Ser/Thr phosphorylation in the N-terminal region of SENP3 in mitotic cells downregulates its deconjugation activity towards topoisomerase TopoIIa through decreasing its interaction with it (Wang et al, 2020;Wei et al, 2018). Different from the above Ser/Thr phosphorylation of SENPs, our study has demonstrated for the first time that in TCR signaling, Lckmediated tyrosine phosphorylation at SENP1 Y270 regulates the binding propensity between SENP1 and the SUMOconjugated substrate and then increases SENP1 isopeptidase activity, while blocking the endopeptidase activity towards pre-SUMO3 but not pre-SUMO1 and in turn enhancing SENP1 peptidase specificity.…”
Section: Discussionmentioning
confidence: 99%